EXPLORATION OF EMPLOYEE EXPERIENCES OF TRANSFORMATIONAL LEADERSHIP IN SHAPING JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Oktapiani, Marliza; Jannah, Wardatul; Nirmayanthi, Andi; Fatmawati, Endang; Syah, Iman (Branding: Jurnal Manajemen dan Bisnis, 2024)
Leadership plays a significant role in shaping employee experiences in the workplace, especially in creating an environment that supports satisfaction and organizational commitment. The interaction between leaders and employees not only influences work motivation but also determines the level of individual loyalty and attachment to the organization. Therefore, a deep understanding of the dynamics of leadership and its impact on employees is essential in efforts to improve organizational performance and sustainability. This study aims to explore how transformational leadership influences employee job satisfaction and organizational commitment through their experiences and interactions in the workplace. This study was conducted using a qualitative approach that allows for an in-depth analysis of employee perceptions and experiences related to leadership in their organizations. Data were obtained from various relevant sources, such as previous research results, and then systematically analyzed to identify key patterns and findings. The results showed that effective leadership plays a role in creating a sense of belonging and employee attachment to the organization. Support, appreciation, and good communication from leaders increase employee job satisfaction and motivation. In addition, responsive and empathetic leadership contributes to long-term employee commitment, which ultimately has an impact on improving organizational performance and stability.